(3HOGjI GdgOGjIs - (3GdYGedj, GdoMQ, GdMQ GdYGedj, eMeO Hf GdMSf Hf Ydj, J (B1104(3g` (B1692(3es ((3eMeO HGbQs)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg QH GdYGdejf (B... (3bO GdJeS efj LeGYI (B... (3Cf CLeY dge eG CbOQ Ydi LeYg ef efUhU GdhGLHGJ hGdeMQeGJ (B... (3ebOeI jLH Ydi Gdecda GdEbQGQ HhLhO Gddg JYGdis
(3BNQgG (B:s
(3BNQgG(B: (3aUd(B: (3jLHaj GdeCeheI GdOjI hcPG GdLGFaI haj GdehVMI YTQ ef GdEHd (B... (3bO PcQJ aj BNQ gPg GdQSGdI GdeageGJ ef GdhGLHGJ hGdeMQeGJ (B... (3GdhGLHGJ Cda hNeS eFI hKdGKjf hGdeMQeGJ CdaG hCQHY eFI hKeGfjI hCQHYjf hjchf GdeLhY KdGKI CdBa EdG SHYI YTQ JbQjkHGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B6: 90s
(3GdPQjYI, L (B3: 33s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis